2021
DOI: 10.3390/cancers13102472
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Carcinomas and Second Malignancies: A Single-Center Review

Abstract: Thymic carcinomas account for less than 0.01% of new cancer diagnoses annually and are more aggressive than thymomas. Autoimmune disorders have been associated with thymomas and only recently with thymic carcinomas. Second malignancies are well described after thymomas. The aim of this study was to analyze the incidence of second malignancies in patients with thymic carcinomas. All cases of thymic carcinomas were identified from the pathology archives of Indiana University. Histological materials were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, a higher incidence of TETs has been reported in multiple endocrine neoplasia type 1 [ 6 ]. Similarly, in patients with TET, several studies have documented rates of second malignancies ranging from 8 to 31%, particularly thymomas [ 7 ]. The prognosis of TET correlates with the histological subtype, with a 5-year overall survival (OS) of ~ 80% and ~ 45% for T and TC, respectively [ 8 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…However, a higher incidence of TETs has been reported in multiple endocrine neoplasia type 1 [ 6 ]. Similarly, in patients with TET, several studies have documented rates of second malignancies ranging from 8 to 31%, particularly thymomas [ 7 ]. The prognosis of TET correlates with the histological subtype, with a 5-year overall survival (OS) of ~ 80% and ~ 45% for T and TC, respectively [ 8 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Previous studies have revealed the association between the incidence of second malignant tumors and thymoma (LeGolvan and Abell 1977 ; Gray and Gutowski 1979 ; Lewis et al 1987 ; Couture and Mountain 1990 ; Wilkins et al 1999 ; Welsh et al 2000 ); because thymic carcinoma and thymic NET are rare, there are few studies on second malignancies arising after diagnosis. Badve suggested that 14 of 85 patients had a second malignancy including embryonal carcinoma, prostatic adenocarcinoma, small cell lung carcinoma, bladder carcinoma, testicular cancer, and so on (Badve et al 2021 ). Hamaji found that the thymic carcinoma patients have a lower cumulative incidence of a second malignancy than thymoma patients.…”
Section: Introductionmentioning
confidence: 99%